KIRKPATRICK EVALUATION ON EDUCATION AND TRAINING OF SCHOOL SUPERVISOR BASED ON BEST PRACTICE, HOTS, AND ADULT EDUCATION IN INDONESIA - Yunus, Renny (International Journal of Psychosocial Rehabilitation, 2020)
Education quality improvement is a joint responsibility that involves various groups, from structural aspects starting from the central level (ministry) to the education unit. Law Number 20 of 2003 on National Education System Article 39 Paragraph 1 states that education personnel have the duty to administer, manage, develop, supervise, and provide technical services to support the education process in educational units. To achieve the National Medium Term Development Plan - Strategic Plan of Directorate General of Teachers and Education Personnel 2015-2019, the Ministry of Education and Culture has set the Average Target of Knowledge and Skills Competency. This purpose of this study was to evalaute the education and training of school supervisor by using Kirkpatrick evaluation. The results of this study recommended that the supervision can be improved by using education and training based on HOTS, Best Practice and Adult Education.